Peer Education's Effect on Girls' Blood Tablet Compliance at SMA 2 Sigi, Dolo - Ervinayanti Ervinayanti; Sudirman Sudirman; Ahmad Yani (PROMOTOR, 2026)
Anemia in adolescent girls remains a significant public health problem in Indonesia, partly due to low adherence to consuming Iron Supplement Tablets (TTD). This study aims to analyze the effect of peer educator education on adherence to consuming TTD in adolescent girls at SMA Negeri 2 Sigi, Dolo District. This research used a quasi-experimental design with a nonequivalent control group design. The sample consisted of 388 female students divided into intervention (n=194) and control (n=194) groups. The intervention group received peer educator education, while the control group received standard education. Data were collected using questionnaires on knowledge, attitudes, practices, and the Morisky Medication Adherence Scale-8 (MMAS-8). Data analysis used the Wilcoxon Signed Ranks Test, Mann-Whitney U Test, and logistic regression. The results showed a significant increase in knowledge, attitudes, practices, and adherence to TTD consumption in the intervention group after peer educator education (p < 0.05). Comparison between the intervention and control groups showed significant differences, with peer educator education having a greater effect on improving adherence. This study concludes that peer educator education significantly improves adherence to consuming Iron Supplement Tablets in adolescent girls. Peer education approaches are recommended as an effective strategy for anemia prevention programs in schools.